Dragon in Protection of Cresent and Red White: Islamic and Nation Thoght of Abdul Karim Oey (Oey Tjeng Hien) - Hartati, Merri Sri; Aulia, Sidiq; Hardiansyah, H (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
The purpose of this paper is to obtain a complete picture of Abdul Karim Oey’s thinking in an Islamic and ethnic context where the boundaries of writing are only a telescope of Abdul Karim Oey’s thoughts on Islam and nationalism. historical research methods, data collection from Heuritics, selection, interpretive, and historiography. Oey’s thoughts about Islam: Islam Universalism, Islam Rationalism in the face of mysticism and ignorance, Islamic Da’wah in assimilation of ethnic Chinese, and his thoughts about Indonesia: disagree with Bung Karno’s ideas about non-Islamic countries and Islamic formalism in the country, love of the motherland and an open mind with true, anti-communist, and national unity in rejecting the federal state created in the Netherlands.